Skeletal and Bone Mineral Density Features, Genetic Profile in Congenital Disorders of Glycosylation: Review - Patryk Lipiński; Karolina M. Stępień; Elżbieta Ciara; Anna Tylki-Szymańska; Aleksandra Jezela-Stanek (Diagnostics, 2021)
Congenital disorders of glycosylation (CDGs) are a heterogeneous group of disorders with impaired glycosylation of proteins and lipids. These conditions have multisystemic clinical manifestations, resulting in gradually progressive complications including skeletal involvement and reduced bone mineral density. Contrary to PMM2-CDG, all remaining CDG, including ALG12-CDG, ALG3-CDG, ALG9-CDG, ALG6-CDG, PGM3-CDG, CSGALNACT1-CDG, SLC35D1-CDG and TMEM-165, are characterized by well-defined skeletal dysplasia. In some of them, prenatal-onset severe skeletal dysplasia is observed associated with early death. Osteoporosis or osteopenia are frequently observed in all CDG types and are more pronounced in adults. Hormonal dysfunction, limited mobility and inadequate diet are common risk factors for reduced bone mineral density. Skeletal involvement in CDGs is underestimated and, thus, should always be carefully investigated and managed to prevent fractures and chronic pain. With the advent of new therapeutic developments for CDGs, the severity of skeletal complications may be reduced. This review focuses on possible mechanisms of skeletal manifestations, risk factors for osteoporosis, and bone markers in reported paediatric and adult CDG patients.